Pengayaan materi Biologi Seluler pada Komunitas Guru Biologi - Adrianto, Hebert; Setyawan , Yuswanto; Banjarnahor, Dharma PP; Kusumah, Irwin Priyatna; Messakh, Billy Daniel (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2023)
Cell biology in schools is important for higher education provision, but it is difficult material for students and teachers to learn because it is abstract. The purpose of this activity is to enrich the concept of cell biology for the Biology Teacher community in the Ciputra Education group. The activity method is carried out by the lecture and discussion method on the Zoom application. The activities proceed according to the agreed-upon schedule. This activity was attended by 15 biology teachers. The results of the activity were that the activity participants had received cellular biology material regarding the cell cycle and cell division, the physiology of sperm formation (spermatogenesis), and muscle contraction. Participants get Shutterstock images and videos from YouTube that have been selected to be used as teaching material in class. The participants' reflections after this activity were that they were able to connect the material with everyday life; Participants can relate the topic of cells to the topics of organ systems, cell metabolism, and genetic material in the biology curriculum for junior high and senior high schools; they were not confused that cell division is actually part of the stages of the cell cycle. Recommendations for further activities from the participants are that this activity will be held again with the topic of the relationship between cells and disease and that it is necessary to measure the participants' knowledge, and need to evaluate the benefits of these images and videos after being applied in class.